Kinerja Inert Gas Generator Untuk Mendapatkan Oksigen Konten 3% Pada Gas Lembam - Susmita Silva; Abdi Seno; Andy Hermanto (LPPM AKMI SUAKA BAHARI CIREBON, 2022)
Inert Gas System is a machine that functions as a security system to prevent explosions on tankers. Explosion prevention is carried out by introducing inert gas into the cargo tank with the aim of reducing oxygen levels in the cargo tank atmosphere so as to prevent the formation of a flammable gas mixture. Inert gas contains very little oxygen, namely 1-2% by volume. The device that produces the inert gas is called the Inert Gas Generator (IGG). The purpose of this study was to determine the factors that cause high oxygen content contained in the inert gas and the efforts made related to the factors mentioned so that the inert gas generator can work optimally. The research method used by the author is descriptive qualitative with Fishbone data analysis techniques and SWOT analysis. The results of the study stated that the factors causing oxygen content of more than 3% were dirty fuel filter, too much combustion air supply, oxygen analyzer that was rarely calibrated, flow sampling was too large, fuel quality was not good, lack of crew knowledge. to PMS (Plan Maintenance System) IGG. Efforts have been made to clean the fuel pump filter, close the air capacity valve a little, calibrate the oxygen analyzer according to the PMS schedule, reduce the sampling valve flow into the oxygen analyzer, add fuel oil treatment (additives) to the fuel, pay attention to the IGG maintenance schedule according to PMS, restore the maintenance implementation system based on the PMS inert gas generator schedule.